I13 overrides resistance mediated by the T315I mutation in chronic myeloid leukemia by direct BCR-ABL inhibition - Gao, Congying; Zhang, Lei; Xu, Yun; Ma, Xiangyu; Chen, Peilei; Chen, Zhe-Sheng; Wei, Liuya (Frontiers in Pharmacology, 2023)
Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm caused by a BCR-ABL fusion gene. Imatinib, has significantly improved the treatment of CML as a first-generation tyrosine kinase inhibitor (TKIs). T315I mutant form of BCR-ABL is the most common mutation that confers resistance to imatinib or the 2nd generation TKIs, resulting in poor clinical prognosis. In this work, we assessed the effect of a potent histone deacetylase (HDAC) inhibitor, I13, on the differentiation blockade in CML cells harboring T315I mutated and wild-type BCR-ABL. We found that I13 possessed highly potent activity against T315I mutated BCR-ABLmutant expressing cells, as well as wild-type BCR-ABL expressing cells. I13 induced cell differentiation and significantly suppressed the proliferation of these CML cells via the cell cycle G0/G1-phase accumulation. Moreover, it was revealed that I13 triggered the differentiation of BaF3-T315I cells was attributed to the block of the chronic myeloid leukemia signaling pathway via the depletion of BCR-ABL mediated by the inhibition of HDAC activity presented by acetylation of histones H3 and H4. Taken together, I13 efficiently deplete BCR-ABL in CML cells expressing BCR-ABL-T315I mutation, which block its function served as a scaffold protein that modulates the chronic myeloid leukemia signaling pathway mediating cell differentiation. The present findings demonstrate that I13 was a BCR-ABL modulator for the development of CML therapy that can override resistance caused by T315I mutated BCR-ABL.